Institutional influences on social enterprise types in the Republic of Ireland - Donnelly Cox, Gemma; Cannon, Sheila; Rhodes, Mary-Lee (My University, 2022)
Extensive research over the past twenty years explains and documents different approaches to and examples of social enterprise across the world. One line of research analyses the institutional contexts – considering economic development, governance, culture, and civil society - in order to explain different national approaches to social enterprise. Simultaneously, researchers have focussed on organisational level features to create typologies of social enterprises. This paper synthesises that research to create an embedded model of types, which sit within and are influenced by institutional contextual factors. The model is tested in the case of the Republic of Ireland, through desk research and empirical observation. A set of 57 organisations provides qualitative data for a narrative account of four types of social enterprise. Contributions include a new model of institutionally embedded social enterprise types which conceptualises and highlights the importance of historical contexts in applying typologies.
PUBLISHED
Keywords: social enterprise typology; Ireland; institutional context; social entrepreneurship; social economy; Identities in Transformation; Inclusive Society; Making Ireland; Nonprofit organisations; Organisation design, development, theory, behaviour; Social Enterprise & Social Entrepreneurship